The Effect of Algebra Box Media on Addition and Subtraction of Algebraic Expressions - Iis Istika; Vikram Yuda Octa Firandhi (ITScience (Information Technology and Science), 2026)
Students’ learning outcomes in algebra, particularly in the addition and subtraction of algebraic expressions, remain relatively low. This problem is mainly caused by students’ limited understanding of like terms, variables, and algebraic operations due to the predominance of conventional teaching methods. Therefore, the use of innovative and concrete learning media, such as the algebra box, is expected to improve students’ conceptual understanding and learning outcomes. This study employed an experimental, quantitative method with a one-group pretest-posttest design. The sample consisted of 14 seventh-grade students of MTs Al-Mizan. Data were collected through pretest and posttest instruments to measure students’ learning outcomes before and after the implementation of the algebra box media. The data were analyzed using the chi-square normality test and the Wilcoxon signed-rank test because the data were not normally distributed. The findings showed a significant improvement in students’ learning outcomes after the implementation of the algebra box media. The average pretest score increased from 37.71 to 85.46 in the posttest. The Wilcoxon test results indicated that Wcount = 105 and Wtable = 21 (? = 0.05), meaning that the null hypothesis (H?) was rejected and the alternative hypothesis (H?) was accepted. The use of algebra box media significantly improves seventh-grade students’ learning outcomes in the addition and subtraction of algebraic expressions at MTs Al-Mizan. This learning media can serve as an effective alternative to support students’ conceptual understanding in algebra.